The relationship between parental report about their children’s obsessive- compulsive disorder symptoms and thought fusion with parent-child relationship structure in adolescents with obsessive-compulsive disorder - Kiani, Ahmadreza; Einy, Sanaz; Rashidi Vala, Zahra; Rashid, Sajjad; jamshidian, Yasaman jamshidian (Researcher Bulletin of Medical Sciences, 2019)
The present study was aimed to examine the relationship between parental report about their children’s obsessive-compulsive disorder symptoms and thought fusion with the parent-child relationship structure among the adolescents with obsessive-compulsive disorder. The research method was correlational descriptive and the statistical population included all the adolescents affected by obsessive compulsive disorder in the City of Ardabil during the 2015-2016 year. The sampling method was available sampling so that 83 patients with obsessive-compulsive disorder were selected from and the questionnaires were implemented on them. The collected data were analyzed using Pearson’s correlation coefficient and multiple regression method. The results showed a significant relationship between the parental report about their children’s obsessive compulsive disorder symptoms and the parent-child relationship structure, but no significant relationship was observed between the thought fusion of the adolescents with obsessive compulsive disorder and the parent-child relationship structure. Therefore, this research showed that using the parental report for detecting OCD in adolescents can be an effective strategy and can be used as a clinical assessment for additional assurance. Also, another important finding highlights the relationship between parent-child relationship structure and parent’s ability to predict their children abnormalities, so investigating family relationships also can be used for better understanding of patient’s problem and needs.